Cardiovascular Determinants of Aerobic Exercise Capacity in Adults With Type 2 Diabetes - Gulsin, Gaurav S. (Diabetes Care, 2020)
OBJECTIVE: To assess the relationship between subclinical cardiac dysfunction and aerobic exercise capacity (peak VO(2)) in adults with type 2 diabetes (T2D), a group at high risk of developing heart failure. RESEARCH DESIGN AND METHODS: Cross-sectional study. We prospectively enrolled a multiethnic cohort of asymptomatic adults with T2D and no history, signs, or symptoms of cardiovascular disease. Age-, sex-, and ethnicity-matched control subjects were recruited for comparison. Participants underwent bioanthropometric profiling, cardiopulmonary exercise testing, and cardiovascular magnetic resonance with adenosine stress perfusion imaging. Multivariable linear regression analysis was undertaken to identify independent associations between measures of cardiovascular structure and function and peak VO(2). RESULTS: A total of 247 adults with T2D (aged 51.8 ± 11.9 years, 55% males, 37% black or south Asian ethnicity, HbA(1c) 7.4 ± 1.1% [57 ± 12 mmol/mol], and duration of diabetes 61 [32–120] months) and 78 control subjects were included. Subjects with T2D had increased concentric left ventricular remodeling, reduced myocardial perfusion reserve (MPR), and markedly lower aerobic exercise capacity (peak VO(2) 18.0 ± 6.6 vs. 27.8 ± 9.0 mL/kg/min; P < 0.001) compared with control subjects. In a multivariable linear regression model containing age, sex, ethnicity, smoking status, and systolic blood pressure, only MPR (β = 0.822; P = 0.006) and left ventricular diastolic filling pressure (E/e′) (β = −0.388; P = 0.001) were independently associated with peak VO(2) in subjects with T2D. CONCLUSIONS: In a multiethnic cohort of asymptomatic people with T2D, MPR and diastolic function are key determinants of aerobic exercise capacity, independent of age, sex, ethnicity, smoking status, or blood pressure.